Soybean yield in future climate scenarios for the state of Rio Grande do Sul, Brazil - Cera, Jossana Ceolin; Streck, Nereu Augusto; Fensterseifer, Cesar Augusto Jarutais; Ferraz, Simone Erotildes Teleginski; Bexaira, Kelin Pribs; Silveira, Waleska Bolzon; Cardoso, Ânthony Paz (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to estimate the yield potential and the water‑limited yield of soybean (Glycine max) in the state of Rio Grande do Sul, Brazil, in two future climate scenarios, SRES A1B and RCP4.5, using the SoySim and Cropgro‑Soybean simulation models. In both models, three maturity groups (4.8, 5.5, and 6.0) and six sowing dates (09/01, 10/01, 11/01, 12/01, 01/01, and 02/01) were considered in the SRES A1B‑CMIP3 and RCP4.5‑CMIP5 scenarios. The analyzed variable was grain yield at 13% moisture (Mg ha-1). Soybean yield potential in Rio Grande do Sul should increase up to the end of the 21st century, according to both scenarios. Water‑limited yield of soybean also increases up to the end of the 21st century, by the SRES A1B‑CMIP3 scenario; however, it will decrease in future periods, by the RCP4.5‑CMIP5 scenario because of limited soil water.